A Case Report of Compound Heterozygosity for β0/β+-Thalassemia Resulting from under Diagnosed β-Thalassemia Found in a Hb A'2 Sample. (2nd January 2019) - Intasai, Nutjeera; Phasit, Ampai; Panyasai, Sitthichai; Pornprasert, Sakorn
Abstract: Hb A'2 (or Hb B2 ) ( HBD : c.49G>C) is the most frequent δ chain variant that has been described in Africa but not in Thailand. We report here a 10-month-old Thai infant with compound heterozygosity for β 0 codon 17 (A>T; HBB : c.52A>T) and β + IVS II-654 (C>T; HBB : c.316-197C>T). Under diagnosed β-thalassemia (β-thal) in her father, who carries Hb A'2 and a heterozygous β 0 codon 17 mutation, and the mother, who carries a heterozygous β + IVS II-654 mutation, was noted. Although Hb A'2 does not cause any problems, heterozygosity for Hb A'2 can lead to under diagnosis of β-thal in Hb A'2 samples. This case highlights the importance of Hb A'2 in prenatal diagnosis (PND). Thus, molecular analysis for β-thal mutations should be carried out when a small peak presents at the retention time (RT) of 4.71 min. on high performance liquid chromatography (HPLC) and the summation level of this peak and Hb A2 was equal or higher than 4.0%.